Novel cryptosystem integrating the Vigenere cipher and one Feistel round for color image encryption - Tabti, Hassan; El Bourakkadi, Hamid; Chemlal, Abdelhakim; Jarjar, Abdellatif; Najah, Said; Zenkouar, Khalid (International Journal of Electrical and Computer Engineering (IJECE), 2024)
The present research will propose an innovative technique for pixel-level encryption of color images. After isolating the R, G, and B channels and converting them into vector mode, an enhanced Feistel network will be applied at the hexadecimal level, facilitated by integrating a substitution table generated from the employed chaotic maps. This is followed by a binary conversion and a shift ensured by pseudo-random vectors. A diffusion function is applied, incorporating another replacement matrix constructed from commonly used chaotic maps in cryptography. This operation links the cipher pixel to the next pixel, thereby reinforcing the avalanche effect and safeguarding the system against any differential attacks. Simulations conducted using our new system on various color images, arbitrarily selected from multiple databases, have yielded satisfactory and highly promising results.